Altered dental plaque microbiota correlated with salivary inflammation in female methamphetamine users - Deng, Zhuohang; Guo, Kaili; Cao, Fengdi; Fan, Tiantian; Liu, Bin; Shi, Mingyue; Liu, Yue; Ma, Zhe (Frontiers in Immunology, 2022)
Poor oral health is the most immediate and overlooked hazard of methamphetamine abuse in humans. Previous studies have reported methamphetamine-associated alterations in saliva microbiota, but the cause of methamphetamine-induced alterations in the oral microenvironment remains unclear.The present study aimed to investigate the alterations in dental plaque microbiota in methamphetamine users, and to explore their relationship with local immune inflammation in the oral cavity. This may provide new ideas on the development of methamphetamine-related oral microenvironment changes. Questionnaires and samples were obtained from 30 female methamphetamine users and 15 sex- and age-matched healthy controls. Microbial profiles of supragingival dental plaque were analyzed using 16S rRNA gene sequencing. Inflammatory factors in saliva were measured using enzyme-linked immunosorbent assay. Methamphetamine users had worse oral self-evaluation. Compared with healthy controls, methamphetamine users showed no differences in oral dental plaque microbial diversity but exhibited differences in the relative abundance of several microbial taxa. At the phylum level, a higher abundance of Proteobacteria and a lower abundance of Firmicutes were detected in methamphetamine users. Moreover, function prediction using the MetaCyc database showed that 33 pathways were significantly upregulated in methamphetamine users; Only the glycolytic (Pyrococcus) pathway was enriched in the C group. Importantly, salivary inflammatory factors showed complex significant associations with bacterial genera in methamphetamine users. Specifically, the genus Neisseria was positively correlated with IL-17 levels in saliva, and both were high in methamphetamine users. In contrast, the genus Streptococcus, with a lower abundance, was positively correlated with lower IL-10 levels. Overall, This study is the first to provide evidence for a link between altered dental plaque microbiota and salivary inflammation in methamphetamine users. Further elucidation of the interactions between methamphetamine use and oral microenvironment would be beneficial for appropriate interventions to improve oral health.